2020
DOI: 10.51791/njap.v46i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary lanthanum oxide (La O ) on the blood characteristics and 2 3 ovarian morphometry of broiler chickens

Abstract: The use of antibiotics as feed additives in animal production has been a source of health concern. A practical approach is the supplementation of animal feeds with rare earth element. Thus, this study was carried out with 225 day – old broiler chicks (CHI strain) to evaluate the influence of dietary Lanthanum oxide (La O ) on the blood characteristics and 2 3 ovarian morphometry. The feeding trial lasted eight weeks before the parameters were determined. The dietary treatments were designated as T , T , T , T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Similarly, Agbede et al ( 2011 ) found that La 2 O 3 (100–300 mg/kg) increased total weight gain and altered heart, spleen, and liver weights. Furthermore, REE supplementation led to changes in hematological and nutritional parameters, including total red blood cell count, hemoglobin and differential leukocytes, cholesterol, and bicarbonate (Agbede et al 2011 ; Ozung et al 2019 ). Two studies (Igbasan and Adebayo 2012 ; Cai et al 2015 ) failed to find increased gain in chick body weight by administering La or Ce or REE mixtures as feed additives at concentrations ranging from 100 to 1500 mg/kg.…”
Section: Rees As Feed Additives In Livestockmentioning
confidence: 99%
“…Similarly, Agbede et al ( 2011 ) found that La 2 O 3 (100–300 mg/kg) increased total weight gain and altered heart, spleen, and liver weights. Furthermore, REE supplementation led to changes in hematological and nutritional parameters, including total red blood cell count, hemoglobin and differential leukocytes, cholesterol, and bicarbonate (Agbede et al 2011 ; Ozung et al 2019 ). Two studies (Igbasan and Adebayo 2012 ; Cai et al 2015 ) failed to find increased gain in chick body weight by administering La or Ce or REE mixtures as feed additives at concentrations ranging from 100 to 1500 mg/kg.…”
Section: Rees As Feed Additives In Livestockmentioning
confidence: 99%